Comparison of Vegetation Index Method to Detect Drought in Bondowoso Regency, East Java - Yuda Aulia Aziz; A Sediyo Adi Nugraha (Universitas Pendidikan Ganesha, 2022)
Drought in Bondowoso County has the potential to occur sustainably with diverse topographic variations. This study aims to determine drought conditions by using a vegetation index with a multi-temporal Landsat 8 OLI image from January-July 2021. The vegetation index methods used are SAVI (Soil Adjusted Vegetation Index), EVI (Enhanced Vegetation Index), and NDVI (Normalized Difference Vegetation Index). The three vegetation indices were chosen because they provide different vegetation sensitivities. The results showed that all three vegetation indices provided a slight difference inaccuracy. SAVI has an accuracy result of 86%, EVI with 14% accuracy, and NDVI has 80% accuracy. The difference in accuracy results from the condition of Bondowoso Regency with a variety of vegetation. Temporally also showed that SAVI is more sensitive to vegetation information, especially in areas close to clouds, than in EVI and NDVI. It can be concluded that SAVI can provide drought information better than EVI and NDVI.